Why Are Reading Difficulties Associated with Mental Health Problems? - Boyes, Mark; Leitao, S.; Claessen, M.; Badcock, N.; Nayton, M. (2016)
A growing literature indicates that children with reading difficulties are at elevated risk for mental health problems; however, little attention has been given to why this might be the case. Associations between reading difficulties and mental health differ substantially across studies, raising the possibility that these relationships may be ameliorated or exacerbated by risk or resilience-promoting factors. Using socio-ecological theory as a conceptual framework, we outline four potential lines of research that could shed light on why children with reading difficulties are at risk of mental health problems and identify potential targets for intervention.